ANALISIS PENGELOLAAN PERPUSTAKAAN JURUSAN PG PAUD DALAM RANGKA MENINGKATKAN EFEKTIFITAS PERPUSTAKAAN SEBAGAI SUMBER BELAJAR BAGI DOSEN DAN MAHASISWA PG PAUD – FIP UNJ - Hartati, Sofia (Perspektif Ilmu Pendidikan, 2009)
The goals of this research were to get information and data on the management and implementation of library in Early Childhood Education Program, Faculty of Education, State University of Jakarta; to exploring the factors that supports the management of libraries in Early Childhood Education Program; and to improve the effectiveness of the library as a learning resource for lecturers and students in Department of Early Childhood Education. The research used descriptive qualitative research method. The results of research indicates that to improve management of the library and the effectiveness of as a learning resource for lecturers and students can get by providing good services to the user. The library services can be done well if supported by all elements of the library such as collections, facilities, professional staff, and awareness of users to use a library. Some improvement at managerial should be done. Thus, the library of Department can act more effectively as a source of learning for lecturers and students of Department of Early Childhood Education, Faculty of Education, State University of Jakarta.